Brahms, the four symphonies - Frisch, Walter, 1951- (Yale music masterworks., 2003)
"Walter Frisch provides a sensitive analytical commentary on the symphonies as well as a consideration of their place within Brahms's oeuvre, within the symphonic repertory of his day, and within the broader musical culture of nineteenth-century Germany and Austria. Frisch also pays particular attention to the evolution of performance style, describing how orchestra size, playing techniques, tempi, and articulation have changed since Brahms's symphonies were first heard."--Jacket